Perlindungan Lingkungan Hidup Dalam Kerangka Ajaran Agama Dan Hukum Hindu - Made Setyawati Apsari; Kade Ayu Santika; Natalia Susilawati (Belom Bahadat, 2026)
The increasing problem of environmental degradation, such as water, soil, and air pollution, as well as the overexploitation of natural resources, demands a comprehensive approach. Environmental protection efforts cannot be achieved solely through technical and legal approaches; they must also be supported by moral and spiritual values ​​that can profoundly shape human consciousness. In this context, Hinduism views the universe as a manifestation of divine power (Brahman), whose sacred nature must be maintained in balance and purity. Humans are positioned as part of nature and as guardians of cosmic harmony. This study aims to examine and analyze the concept of environmental protection within the framework of Hindu religious teachings and law. The research method used is normative legal research with a theological and philosophical approach, through a study of Hindu scriptures and legal sources. The main concepts analyzed include dharma, rta, yadnya, Tri Hita Karana, Rwa Bhineda, and the normative provisions contained in the Manawa Dharmasastra that regulate the prohibition of environmental pollution and destruction. The study's findings indicate that Hindu religious teachings and law explicitly affirm human obligations to preserve nature and prohibit actions that disrupt environmental balance. From a Hindu perspective, environmental protection is part of the implementation of religious, moral, and ethical dharma. Therefore, the values ​​of Hindu teachings and law have strong relevance as a normative and ethical foundation for strengthening ecological awareness and supporting environmental protection efforts in the modern era.